Analisis Peran Dinas Sosial dalam Menanggulangi Kemiskinan di Kabupaten Bengkulu Selatan - Adi Putra, Muklas; Darmi, Titi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
This research aims to determine the role of the Social Service in alleviating poverty in South Bengkulu Regency. The method used in this research is a qualitative method, collecting field data using observation, interviews and documentation. Meanwhile, in data analysis, researchers used techniques proposed by Miles and Huberman (1992) who stated that activities in qualitative data analysis were carried out interactively and continued continuously until completion. The activities carried out in data analysis were: data collection, data reduction, presenting data, drawing conclusions and verifying data. The informants in this research consisted of 6 employees of the South Bengkulu Regency Social Service. Based on the research results, it is known that the South Bengkulu Regency Social Service has tried quite well to overcome existing poverty. This can be seen from the poverty rate in South Bengkulu which continues to decline every year, such as in 2021 the poverty rate was 18.54%, in 2022 it was 17.86%, and in 2023 it was 17.51%. The roles in question are: Facilitator Role, Educational Role, Representative Role, and Technical Role. From the results of this research, it can be concluded that the role of social services as a social institution that plays a role in alleviating poverty has been implemented well enough to reduce the poverty rate in South Bengkulu District every year. The roles in question are: facilitator role, educational role, representative role, technical role.